Practical English For Global Competitiveness : 10 - Que, Glenda B. (Sampaloc, Manila. St. Augustine Publications, Inc., 2020)
"This textbook is written to address these issues since this book is user-friendly. Each topic in this book is intesively elucidated with its explanation and examples provided for easy understanding, independent learning, and making meaning purposes of whomever the user is. It is designed based on the K to 12 curriculum to help students improve their competencies on listening comprehension, oral language and fluency, reading comprehension, literature, vocabulary development, viewing comprehension, grammar awareness, and writing and composition to proficiently interact with other".
Includes bibliography.
English text.
Keywords: Literature